EVALUATION OF ANGIOGENESIS IN IDIOPATHIC MYELOFIBROSIS WITH CD31 AND CD34 BY LIGHT MICROSCOPE AND COMPUTER-AIDED IMAGE ANALYSIS SYSTEM. (Iraqi Journal of Medical Sciences, 2016)
Background: Myelofibrosis with myeloid metaplasia (MMM) is a clonal stem cell disease with varying degrees of fibrosis in the marrow.Vasculogenesis is the formation of new blood vessels from pre-existing vessels during adult life; it plays a critical role in neoplastic development, progression and metastasization and has been shown to be an adverse prognostic factor in many solid tumors.It is becoming increasingly evident that angiogenesis plays a key role in the pathophysiology of hematologic malignancies by estimating bone marrow microvessel density and by measuring circulating angiogenic factors. MMM is probably the disease with the more pronounced angiogenesis among Chronic Myeloproliferative Disorders.Objective:1. Evaluation of angiogenesis in Idiopathic Myelofibrosis (IMF) via immunohistochemical staining for CD31 and CD34 and quantifying them by Computerized Image Analysis System and Light Microscope.2. To investigate whether angiogenesis can be considered as a marker for disease activity.Methods: This cross sectional study was conducted on 31 formalin fixed paraffin embedded blocks of Idiopathic Myelofibrosis cases along with 10 age matched control cases having no abnormal bone marrow pathology, from January 2006 to June 2006. The sections from bone marrow biopsies were processed routinely and stained with Hematoxylin and Eosin (H&E) and with immunohistochemical stain for CD31 and CD34 markers. The bone marrow Microvessel Density of IMF and control case was assessed by the means of Computer Aided Image Analysis System and by visual count using light microscope.Results: This study revealed that there was a significant increase in microvessel density in IMF cases, using both the computerized method and the visual count by light microscope, with both CD31 & CD34 compared to control group (P < 0.05). Also this study showed that the increase in angiogenesis was positively correlated with the Dupreiz score prognostic system and the age of the patients.On the other hand; no significant correlation was found between angiogenesis and the following parameters: sex of the patient, Hb value, WBCs count, peripheral blood platelets count.Conclusion: This study has showed that angiogenesis was an integral component of the bone marrow stromal reaction in MMM and it was closely related to many prognostic parameters; thus bone marrow angiogenesis can be used as a tool to assess the disease activity.Key word: Idiopathic myelofibrosis, angiogenesis, Computeriz image analysis.
Keywords: Idiopathic myelofibrosis; angiogenesis; Computeriz image analysis